Live Experiences in the Theater Gardens of Contemporary Art: Affective Curating and Exhibition Experiments with Theatricality - Sprogøe, Charlotte (Peripeti, 2022)
Theatre has been a model for curatorial experiments throughout the history of experimental exhibitions. This article will look into contemporary experiments with curating exhibition formats that come alive as virtual, ‘lucid dreams’ through the uses of theatrical tropes such as Narrator, Stage, Backdrop – and through the integration of affect, living matter, organic form and worldlike backdrops into the formats, as in the historic Theater Gardens.